Analysis of the Supply Elasticity in Basic Formal Education - Lozano Galindo, Oscar Leonardo (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The permanence and graduation of official basic education in Colombia is an educational public policy issue that encompasses the exercise of the right and the externalities generated by the formation of highly qualified human capital in a low-income society. Thus, the objective of this work was to analyse the elasticity of the supply of official basic education through a systematic review of terms related to supply-demand elasticity, under the premise that it is a free service; the result determined that the supply is sensitive to the budget, as well as to the number of teachers attending the educational service, but does not show a relationship with improvement in educational quality.